Kebugaran Jasmani Siswa Pendidikan Dasar dan Menengah di Jawa Barat - Agus Amin Sulistiono (Jurnal Pendidikan dan Kebudayaan, 2014)
This research is intended to assess the physical fitness of primary school, junior secondary school and senior secondary school students based on gender and class level. Data collection was conducted by cross-sectional in Bandung and Majalengka, with a sample of 721 students, were taken by purposive cluster sampling. Processing and analysis of data in the form of descriptions and inferential statistics.The result of research shown that: 1) The level of physical fitness of primary school students still have low physical fitness were 42.27 percent, while the junior secondary school students were 36.87,and senior secondary school student were 46.11 percent. physical Fitness of primary school students, for both male and female students, the higher the class the higher their level of physical fitness, while at the junior secondary school level, for male students the higher theclass the higher its physical fitness, for female student the physical fitness stays the same regardless of their class. For senior secondary school students, both boys and female student, their physical fitness remain same regardless of their class. It can be concluded that the higher the education level of students the more diminished their physical activity,the implication is the declining of their physical fitness.